Isolation and screening of probiotic candidates from marron, Cherax cainii (Austin, 2002) gastrointestinal tract (GIT) and commercial probiotic products for the use in marron culture - Ambas, I.; Buller, N.; Fotedar, Ravi (Wiley-Blackwell Publishing Ltd., 2015)
Six strains of bacteria including Bacillus mycoides (A10) and Shewanella species (A12) isolated from healthy marron intestine, Bacillus species (PM1), Bacillus subtilis (PM3), Bacillus sp. (PM4) and Bacillus sp. (AQ) from commercial probiotic products were investigated for probiotic potential in marron culture. Antibiotic susceptibility tests indicated PM3 and PM4 were susceptible to all nine antibiotics evaluated. A10, A12 and AQ were resistant to class penicillins, whereas PM1 was resistant to class penicillin and macrolides. All strains were non-pathogenic for marron. Strong inhibition against Vibrio mimicus and Vibrio cholerae non-01 was exhibited by PM4 and PM3. A10 inhibited V. mimicus at 72 h of growth, but not V. cholerae non-01, whereas A12 inhibited V. cholerae non-01 but not V. mimicus, and AQ showed no inhibition activity. A wide range of enzymes were produced by A10 and AQ using the API ZYM test. Protease enzymes were produced by PM3, PM4, AQ and PM1. In order of effectiveness, the following bacteria have probiotic potential: B. subtilis (PM3), Bacillus sp. (PM4) and B. mycoides (A10). Further study is required to determine the bacterium or any combination that gives a multibeneficial effect on marron.